Children Rights and The Age Limit: The Ruling of The Indonesian Constitutional Court - Hermanto, Bagus; Yusa, I Gede (Kertha Patrika, 2018)
Indonesian laws determines different age limit for the children. The Law of Republic of Indonesia Number 1 Year 1974 concerning Marriage holds the age limit for the children until 16 years old for the women and 19 years old for the men. Meanwhile, on the Law of Republic of Indonesia Number 23 Year 2002 concerning Child Protection, the age limitation both for women and men is 18 years old. This Child Protection Act has adopted norm as stipulated in the Convention of the Rights of Children, as ratified through Presidential Decree Number 36 Year 1990. Some violations of the human right of children in Indonesia were more or less related to the unclear limitation of the age of children. A few years ago, this situation was brought into legal concern as a constitutional review was lodged before the Constitutional Court of Republic of Indonesia. This court has finally issued a Judgment Number 30-74/PUU-XII/2014 that addressing the issue in concern. Once should be noted that not all Justices had a similar opinion on the Judgment as one Justice expressed a different opinion. The main purpose of this paper is to analyze the legal consideration contained in this Judgment. In addition, it also intends to criticize the Justice’s Dissenting Opinion that was addressed against this Judgment. This paper is set as a Normative Legal Research that uses case study approach and statutory approach. Key Words      : Constitutional Court, Indonesia, Children Rights, Age Limit.